InteractiveROSETTA: a graphical user interface for the PyRosetta protein modeling suite. (26th August 2015) - Schenkelberg, Christian D.; Bystroff, Christopher
Abstract : Summary: Modern biotechnical research is becoming increasingly reliant on computational structural modeling programs to develop novel solutions to scientific questions. Rosetta is one such protein modeling suite that has already demonstrated wide applicability to a number of diverse research projects. Unfortunately, Rosetta is largely a command-line-driven software package which restricts its use among non-computational researchers. Some graphical interfaces for Rosetta exist, but typically are not as sophisticated as commercial software. Here, we present InteractiveROSETTA, a graphical interface for the PyRosetta framework that presents easy-to-use controls for several of the most widely used Rosetta protocols alongside a sophisticated selection system utilizing PyMOL as a visualizer. InteractiveROSETTA is also capable of interacting with remote Rosetta servers, facilitating sophisticated protocols that are not accessible in PyRosetta or which require greater computational resources. Availability and implementation: InteractiveROSETTA is freely available at https://github.com/schenc3/InteractiveROSETTA/releases and relies upon a separate download of PyRosetta which is available at http://www.pyrosetta.org after obtaining a license (free for academic use). Contact: bystrc@rpi.edu